KELOMPOK RISET (KERIS): STRATEGI PENINGKATAN PUBLIKASI ILMIAH BAGI DOSEN DI JURUSAN AKUNTANSI FE UNNES - Risanda A. Budiantoro; Kiswanto Kiswanto; Fitrarena Widhi Rizkyana; Richatul Jannah (LP2M Universitas Ibrahimy, 2023)
There still needs to be a higher level of participation as a lecturer in implementing the Tridharma of Higher Education in producing scientific publications. One solution is to initiate the Kelompok Riset (Keris) to increase scientific publications for lecturers, especially lecturers in the Accounting Department, FE UNNES. The approach method used in this community partnership program is AKPL Criteria, USG Analysis, Fishbone Analysis, and Mc Namara Filtering Technique Analysis for determining priority issues and root causes of problems. In addition, the 7M Analysis and Constraint-Solution-Recommendation Analysis were used to prepare and implement Kelompok Riset (Keris)’s technical guidebook. As a result, the Kelompok Riset (Keris) can become the smallest format unit in the technical implementation and substance of research activities by lecturers of the Accounting Department to facilitate the planning, implementation, monitoring, and evaluation of research activities. Hopefully, It will spearhead the reputation of the Accounting Department, Faculty of Economics, Universitas Negeri Semarang on a national and international scale. So the lecturers of the Accounting Department can achieve the targets of articles for publication in Scopus-indexed journals that the faculty has set.